Self-Discovery and Individuation Process in Matt Haig’s The Midnight Library - Daimatus Sholikhah; Anita Rahmah Dewi (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2025)
This research aims to analyze the process of self-discovery and individuation of the main character in Matt Haig's novel "The Midnight Library" using Carl Jung's analytical psychology. The background of this research is based on issues of depression, regret, and the search for the meaning of life, which are the core conflicts of the main character, Nora Seed. This research employs a context-oriented approach with close reading techniques of narrative and conversation in the novel. The results show that Nora's self-discovery process begins with awareness of her shadow, including guilt, trauma, and past regrets. This process develops into individuation as Nora accepts these aspects and integrates the conscious and unconscious parts of herself. Nora's final decision to return to living life as it is marks her success in achieving wholeness, which also improves her mental health and emotional well-being.